Pengaruh Bising Pesawat Udara terhadap Jumlah Sel NK (CD56 + CD16 + CD3 ) pada Masyarakat di Sekitar Bandara Adi Sumarmo Boyolali - Hartono, Hartono (Lembaga Penelitian Universitas YARSI, 2008)
Exposure to noise constitutes a health risk. There is sufficient scientific evidence that noise exposure can induce hearing impairment, hypertension and ischemic heart disease, annoyance, sleep disturbance, and decreased school performance. For other effects such as changes in the immune system and birth defects, the evidence is limited.The aims of this study was to find out the effect of the aircraft noise level to the number of Natural Killer Cell (CD56+CD16+CD3) among people in the area of Adi Sumarmo Airport Boyolali.The research finding was expected to contribute to the science development and to give benefits for local government and among people in the Area of Adi Sumarmo Airport in preventing the effect of noise. The research design was an analytical survey with a cross sectional approach, taking location at the Dibal and Gagak Sipat Village, Ngemplak Sub district, Boyolali District. The work was conducted from Juny to October 2008. The number of subjects involved were 57. They were divided into 3 groups; Group 1 was exposed 52.17 dB of noise level (19 respondents); Group 2 was exposed 71.79 dB of noise level (19 respondents); and Group 3 was exposed 92.29 dB of noise level (19 respondents). The samples were taken usingsimple random sampling. The data were analyzed by Anova followed by Post Hoc Test using LSD test completed with Homogenous Subsets. Based on the results of the analysis, a conclusion was drawn that there was a significant effect of the aircraft noise level to the number of Natural Killer Cell (CD56+CD16+CD3) among people in the area of AdiSumarmo Airport Boyolali.